Spatial variability of soil chemical properties and its effect on crop yields: a case study in maize (zea mays l.) on the bogota plateau (2011)
To evaluate the effect of soil chemical properties on the crop yield of corn, in the context of site-specific fertilization, it was characterized the spatio-temporal variability of these properties and crop yield in a lot at the Centro Agropecuario Marengo of the Universidad Nacional de Colombia (Mosquera, Colombia). Using a systematic sampling grid of 32 points (25 x 25 m), soil samples were taken before crop sowing and 60 days after sowing (das) to determine soil pH, N (%); Ca, K, Mg, Na, Al, H (cmol+ kg-1), P, Cu, Fe, Mn, Zn and B (mg kg-1). At 162 das, harvest and yield components were evaluated by site. The data was processed using multivariate procedures, descriptive analysis and geostatistical analysis. Emergent properties were obtained from the original chemical variables using principal component analysis (PCA); these new variables were evaluated using geostatistical analysis to show spatial distribution and its correlation with crop yield. The PCA allowed the finding of three patterns of spatial variability in the soil corresponding to the variables related to soil fertility OC, Ca, Mg, K, CIC and B, the availability of nutrients by soil redox potential, and the variability associated with salinity explained by the Na content and soil electrical conductivity. The first group of variables largely explains the spatial variability of crop yield of corn.